Nanopore-Templated Silver Nanoparticle Arrays Photopolymerized in Zero-Mode Waveguides - Han, Donghoon; Crouch, Garrison M.; Chao, Zhongmou; Fullerton-Shirey, Susan K.; Go, David B.; Bohn, Paul W. (Frontiers in Chemistry, 2019)
In situ fabrication of nanostructures within a solid-polymer electrolyte confined to subwavelength-diameter nanoapertures is a promising approach for producing nanomaterials for nanophotonic and chemical sensing applications. The solid-polymer electrolyte can be patterned by lithographic photopolymerization of poly(ethylene glycol) diacrylate (PEGDA)-based silver cation (Ag+)-containing polyelectrolyte. Here, we present a new method for fabricating nanopore-templated Ag nanoparticle (AgNP) arrays by in situ photopolymerization using a zero-mode waveguide (ZMW) array to simultaneously template embedded AgNPs and control the spatial distribution of the optical field used for photopolymerization. The approach starts with an array of nanopores fabricated by sequential layer-by-layer deposition and focused ion beam milling. These structures have an optically transparent bottom, allowing access of the optical radiation to the attoliter-volume ZMW region to photopolymerize a PEGDA monomer solution containing AgNPs and Ag+. The electric field intensity distribution is calculated for various ZMW optical cladding layer thicknesses using finite-element simulations, closely following the light-blocking efficiency of the optical cladding layer. The fidelity of the polyelectrolyte nanopillar pattern was optimized with respect to experimental conditions, including the presence or absence of Ag+ and AgNPs and the concentrations of PEGDA and Ag+. The self-templated approach for photopatterning high-resolution photolabile polyelectrolyte nanostructures directly within a ZMW array could lead to a new class of metamaterials formed by embedding metal nanoparticles within a dielectric in a well-defined spatial array.